System Biology Approach for Cardiovascular Medicine - Mariano, Cibelle (2015)
Objectives: This research project proposes the study of interactions between biological, including genetics, and environmental factors that give rise to the cardiovascular risk profile as well as to characterise the genetic cardiovascular risk profile of the Portuguese population. It is also proposed to study the differential expression pattern between a control and disease premature myocardial infarction) population in order to identify novel biomarkers for the early identification of at risk subjects. e results should have a high impact on the definition of criteria for identifying individuals at high risk of developing cardiovascular disease.